ENT secrets - Scholes, Melissa A.; Ramakrishnan, Vijay R. (Elsevier, 2016)
Stay up to date on the broad specialty of otolaryngology with ENT Secrets, the revised volume in the popular Secret Series. This medical reference book reviews the overal field of otolaryngology, with each chapter covering basic and in-depth subjects, important topics for a wide-range of practitioners, and practical management issues.